(3GSJQGJjLjGJ hYedjGJ GdEOGQI (B/s - (3GdedjLj, YHO GdgGOj GHQGgjes ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2002)
(3GdeONd dOQGSI GdEOGQI GdYGeI , efGgL heOGNd OQGSI GdEOGQI GdYGeI , GdeUWdMGJ hGdeaGgje GdYdejI ddEOGQI GdefXeI , GdEOGQI hXGFagG hYedjGJgGs
(3GdeQGLY U(B.349s
Keywords: (3GdEOGQI GdYGeIs